From shelf to abyss: Record of the Paleocene/Eocene-boundary in the Eastern Alps (Austria) - H. EGGER; C. HEILMANN-CLAUSEN; B. SCHMITZ (Geologica Acta, 2009)
In the Eastern Alps (Austria) several marine successions, which were deposited ranging from shallow shelf to bathyal slope and abyssal basin, provide detailed records across the Paleocene/Eocene-boundary. These records indicate a two-step event starting with a prominent sea-level fall and followed by climatic changes. At the northern and southern shelves that fringed the Penninic Basin, the shallow-water sedimentary records are incomplete across the Paleocene/Eocene transition. Erosional surfaces indicate a major sea-level drop, which was terminated by an early Eocene (Ypresian) transgression within calcareous nannoplankton Zone NP12. As a proxy for the onset of this sea-level fall a strong increase in the terrestrially-derived input into the Penninic Basin can be used. The abyssal Anthering section from the northern part of the basin comprises a complete succession from NP9 to the upper part of NP10 (upper Thanetian-lower Ypresian). The thickest turbidite beds of this 250m thick succession appear just before the carbon isotope event in the upper part of zone NP9, which is used to recognize the Paleocene/Eocene-boundary. A major lithological change from a sandstone-dominated facies to a claystone-dominated facies occurs at the onset of the carbon isotope event. This might be the result of a climatic change, resulting in increased intra-annual humidity gradients and increased physical erosion of the hinterland. Consequently, mainly fine-grained suspended material would have come into the basin and caused an increase in hemipelagic sedimentation rates by about a factor of 6. A similar value has been calculated for the bathyal Untersberg section, which was deposited on the southern slope of the basin, where an increased input of siliciclastic material is associated with a carbonate dissolution event during the carbon isotope event. At the southern shelf, a stratigraphic gap within the Gosau Group in the Krappfeld area (Carinthia) comprises the Maastrichtian and Paleocene. After a sea-level rise nummulitic marlstone and limestone were deposited in the lower part of zone NP12. Since the northern and southern shelves of the Penninic Basin belonged to different tectonic domains, with different potentials of crustal subsidence, the temporal similarity of sea-level changes on both shelves in the latest Paleocene and earliest Eocene suggests that these sea level fluctuations were mainly eustatic in origin.